2020
DOI: 10.1186/s41936-020-00169-9
|View full text |Cite
|
Sign up to set email alerts
|

The protective effect of propolis against aluminum chloride-induced hepatorenal toxicity in albino rats

Abstract: Background: The use of natural products is an essential way to new pharmaceutical leads for the discovery and development of new drugs to treat diseases. Propolis (Pro) is a natural resinous product produced by honey bees. It has a strong cytoprotective effect against various exogenous toxic agents. The current study was designed to evaluate the possible protective effect of propolis against the toxicity of aluminum chloride (AlCl 3) on hepatorenal structure and function in male white albino rats. Methods: Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 41 publications
8
12
0
Order By: Relevance
“…The protective effect of propolis was confirmed by estimating the serum testosterone level which showed a highly significant increase in case of AlCl3+propolis-treated group. Consistent with the present results, previous reports confirmed the protective effects of propolis against AlCl3-induced hepatorenal toxicity in male rats [25]. Moreover, propolis has been shown to ameliorate sperm quality, reproductive organs and antioxidant status of male rats treated with cyclosporin-A [26].…”
Section: Discussionsupporting
confidence: 93%
“…The protective effect of propolis was confirmed by estimating the serum testosterone level which showed a highly significant increase in case of AlCl3+propolis-treated group. Consistent with the present results, previous reports confirmed the protective effects of propolis against AlCl3-induced hepatorenal toxicity in male rats [25]. Moreover, propolis has been shown to ameliorate sperm quality, reproductive organs and antioxidant status of male rats treated with cyclosporin-A [26].…”
Section: Discussionsupporting
confidence: 93%
“…Nonetheless, these histopathological changes were reduced in the kidney of rats treated with propolis consequently, mild degeneration and less necrosis in renal tubules appeared with propolis as well as, normal renal corpuscles. Our ndings were in agreement with Garoui et al, (2012); Soliman et al, (2015); Okail et al, (2020).…”
Section: -3-histopathological Effectssupporting
confidence: 91%
“…At the same time, there was relative damage reduction in the propolis group which displayed reduction in liver damages markers that converted to; mild dilation of blood sinusoids, mild vacuolation of hepatocytes and intact endothelium of central vein. Similar observations were reported by; García-Niño & Pedraza-Chaverrí, (2014) and Okail et al, (2020). Additionally, there were renal damages in the contaminated heavy metals group appeared in, degenerated glomerulus with hyaline cast and degenerated renal.…”
Section: -3-histopathological Effectssupporting
confidence: 88%
“…These results go on hand with the findings of El-Haskoury et al [26] who reported that honey exhibited strong hepatoprotective action against CCL4-induced toxicity. Likewise, propolis extract (150 mg/kg BW) was found able to prevent kidney injury and renal dysfunction induced by aluminum chloride in rats [17].…”
Section: Effect Of Interventions On Liver Functionmentioning
confidence: 94%
“…Several reports have documented that propolis extracts possess a broad spectrum of pharmacological actions such as antidiabetic, antimicrobial, and antitumoral effects [15,16]. Moreover, it was discovered that propolis has a potent protective action in kidney and liver damages [17] which makes it an ideal preventive candidate against GENT adverse effects. It is well documented that the antioxidant capacities of natural products, including beekeeping products, are mostly associated with in vivo activities [18].…”
Section: Introductionmentioning
confidence: 99%